2012
DOI: 10.1039/c2cp42797d
|View full text |Cite
|
Sign up to set email alerts
|

Limits of metastability in amorphous ices: the neutron scattering Debye–Waller factor

Abstract: Recently, it became clear that relaxation effects in amorphous ices play a very important role that has previously been overlooked. The thermodynamic history of amorphous samples strongly affects their transition behavior. In particular, well-relaxed samples show higher thermal stability, thereby providing a larger window to investigate their glass transitions. We here present neutron scattering experiments using fixed elastic window scans on relaxed forms of amorphous ice, namely expanded high density amorpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…The thermal stability of eHDA compared with the other states was shown in the literature in many different ways. Although different experimental methods, such as neutron scattering [27,54], calorimetric measurements [10] and dielectric spectroscopy [40] show the same trend, the absolute values differ slightly due to every method using not only a different observable but also different heating rate, due to experimental restrictions. In the current study, we now compared different heating rates within the same experimental method and found that when using a 10× faster heating rate of 4 K min −1 , the conversion appears distinct both for the HDA-like state starting from VHDA and eHDA 0.07 (figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The thermal stability of eHDA compared with the other states was shown in the literature in many different ways. Although different experimental methods, such as neutron scattering [27,54], calorimetric measurements [10] and dielectric spectroscopy [40] show the same trend, the absolute values differ slightly due to every method using not only a different observable but also different heating rate, due to experimental restrictions. In the current study, we now compared different heating rates within the same experimental method and found that when using a 10× faster heating rate of 4 K min −1 , the conversion appears distinct both for the HDA-like state starting from VHDA and eHDA 0.07 (figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Quasielastic neutron scattering measurements on LDA-I and uHDA previously showed the absence of such fast precursor processes 100 . Recently these experiments were repeated using LDA-II and eHDA 89 . The Debye-Waller factor shows a very weak sub-T g anomaly in some of the samples, which might be the signature of fast precursor dynamics and hence a signature for a glass transition.…”
Section: Structure Of Water In the Liquid Statementioning
confidence: 99%
“…This has been out of reach in research on amorphous ices so far even though calorimetry methods reaching heating rates on the order of 10 5 K/s were employed to study them [31,32] . However, it has been possible to study whether or not a glass transition can be observed upon heating amorphous ice prior to crystallization and/or prior to the transformation to other amorphous ices [20,31–44] . This glass transition would lead to an ultraviscous liquid state which is also called deeply supercooled liquid water.…”
Section: Introductionmentioning
confidence: 99%